2005
DOI: 10.1002/bies.20215
|View full text |Cite
|
Sign up to set email alerts
|

MHC‐I recognition by receptors on myelomonocytic cells: New tricks for old dogs?

Abstract: Receptors on cytotoxic T lymphocytes and natural killer cells play well-established roles in the immunological response and share a common ligand in the form of MHC-I. We discuss how a variety of MHC-I receptors are also expressed on myelomonocytic cells such as macrophages and dendritic cells. Since myelomonocytic MHC-I receptors recognise a broad range of alleles and MHC-I structures, we propose that their task is to discern expression levels and folding forms of MHC. We describe a model in which these recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…In addition to the 'classical' functions, they may also serve as either negative or positive regulators of NK cell function through engagement of killer inhibitory receptors (KIRs) [60]. Recent hypotheses also proposed their role in differentiation and cytokine production of antigen-presenting cells of myelomonocytic origin [61]. Some of these old and new functions of MHC molecules are summarized in Fig.…”
Section: Structural and Functional Variety Of Classical And Non-classmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the 'classical' functions, they may also serve as either negative or positive regulators of NK cell function through engagement of killer inhibitory receptors (KIRs) [60]. Recent hypotheses also proposed their role in differentiation and cytokine production of antigen-presenting cells of myelomonocytic origin [61]. Some of these old and new functions of MHC molecules are summarized in Fig.…”
Section: Structural and Functional Variety Of Classical And Non-classmentioning
confidence: 99%
“…In addition to the various interactions and functions of MHC molecules listed in Table 1, stably expressed non-classical forms of MHC-I derived from classical MHC-I gene products, such as ␤2-microglobulin-free heavy chains (FHC), are also expressed in infected, transformed or activated lymphoid or myeloid cells [62][63][64] and may exert specific regulatory functions [61,[63][64][65] (see next chapter).…”
Section: Structural and Functional Variety Of Classical And Non-classmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfolded HLA class I molecules are a feature of activated lymphocytes (41)(42)(43)(44)(45)(46)(47) and their recognition and functions are of growing interest (45,48). The inhibitory receptor LILRB2 can bind to b 2 m-free forms of both the HLA-B27 allele as well as the nonclassical HLA-G molecule (20,23).…”
mentioning
confidence: 99%
“…Supporting this view is a recent study showing that HLA-G could form homodimers through the intermolecular Cys 42 -Cys 42 disulfide bond, which exhibited higher overall affinity to leukocyte Ig-like receptor subfamily B (LILRB) 1/2 than the monomer by significant avidity effects as a result of enhancing the LILRB1-mediated signaling at the cellular level (17,18). Relevant to this point are several studies that suggested that HLA-B27 can form a Cys 67 -dependent HC homodimer in the absence of b 2 m, and dimerization might be implicated in the inflammatory arthritis observed in ankylosing spondylitis, through interactions with LILR and KIR present on lymphomyeloid cells (19)(20)(21). Additionally, one recent study demonstrated that exosomes can display a significant proportion of their MHC I content in the form of disulfide-linked MHC I dimers, which may be novel structures for recognition by immune receptors (22).…”
mentioning
confidence: 99%